Mathematical problems that lead to investigate in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article presents some mathematical problems for late kindergarten or first cycle primary levels. These problems have several possible solutions and some solving strategies are presented. It is important to introduce these problems as soon as possible and make students learn how to investigate and solve problems, from the very beginning.
Keywords: Mathematics; Mathematical competence; Early Childhood Education; Problem solving; Research